Literary Autobiography Between Authenticity And Modernity Critical Analytical Study - Muhamad Ata, Awatef El Badri (Ijaz Arabi Journal of Arabic Learning, 2024)
This research paper is based on a conception of “literariness” in heritage as a product of the mechanisms upon which the art of writing autobiographies in Arabic literature is based, searching for its foundational roots in the depths. They are looking for the reason for its continuation and preservation as a genre of ancient and renewed literary genres and an important spatial text in scholarly and social life. It is open to more than one reading; it has undergone some transformations and developments throughout the ages to search for excellence in two literary works – Kitab Alawraq by Abu Bakr Al-Souli (335 AH), Mathaq Alsabr by Muhammad Eid Al-Araimi (1954 AD), analyzing their private memoirs, with which they penetrated the stable cultural pattern, revealing what they combine and distinguish themselves with, whether in the form of the covert translation of Al-Souli. In this way, the pleasure of remembering represents a translation of the state of power and wealth. There is a connection to the space of higher authority; writing the autobiography is a subject of pride for Al-Souli. It represents an outlet for the psychological source from the state of lack and brokenness, or being a narrative vision that the writer transferred from its realistic structure, in which sadness and despair dominate the self, to a new imaginative artistic structure. This structure is rich in cultural heritage and symbolic production, filled with optimism and bright aspects of life. In both cases, it is considered a basis for re-reading the news in the light of authenticity and modernity.